Humor Discourse Structure: A Political Communication Strategy - Risnawati, Eris; Gunawan, Wawan; Fatinova, Dede; Mubarok, Yasir (SCOPE: Journal of English Language Teaching, 2024)
Language phenomena during political years are always extraordinary. Drama is a constant presence, both online and offline, manifesting in various forms such as social media or real-life situations. Despite the inevitability of this problem due to the unavoidable nature of the election season, some deputy candidates are diligently creating political communication strategies to gain acceptance from the broader society. It is essential to comprehend these strategies collectively to ensure that the selected representatives do not consistently project an unfavorable image. Prior research has indeed been conducted on political communication and humor, but as distinct areas of study. This research combines the concept of humor with transitivity theory to thoroughly and precisely investigate the data. The approach employed is qualitative, underpinned by Halliday's transitivity theory and van Dijk's critical discourse analysis. The data source is the legislative interview (wawancaleg) on the channel @Abdel.Achrian. The data were collected using the observation method, which involved the basic technique of listening and the advanced technique of taking notes. The analysis reveals that the predominant structure of political communication discussion in the legislative interview program, hosted by Abdel Achrian, is characterized by material and mental processes. The material and mental processes achieve equilibrium between the physical and the mental, creating a demeanor that is both calm and earnest. The reader can infer that this pattern is applicable to speech patterns characterized by a relaxed or non-stiff expression, but nevertheless conveying a serious impression.